IDH1R132H Mutation Increases U87 Glioma Cell Sensitivity to Radiation Therapy in Hypoxia. (7th May 2014) - Wang, Xiao-Wei; Labussière, Marianne; Valable, Samuel; Pérès, Elodie A.; Guillamo, Jean-Sébastien; Bernaudin, Myriam; Sanson, Marc
Abstract : Objective . IDH1 codon 132 mutation (mostly Arg132His) is frequently found in gliomas and is associated with longer survival. However, it is still unclear whether IDH1 mutation renders the cell more vulnerable to current treatment, radio- and chemotherapy. Materials and Methods . We transduced U87 with wild type IDH1 or I D H 1 R 132 H expressing lentivirus and analyzed the radiosensitivity (dose ranging 0 to 10 Gy) under normoxia (20% O2 ) and moderate hypoxia (1% O2 ). Results . We observed that I D H 1 R 132 H U87 cells grow faster in hypoxia and were more sensitive to radiotherapy (in terms of cell mortality and colony formation assay) compared to nontransduced U87 and IDH1 wt cells. This effect was not observed in normoxia. Conclusion . These data suggest that I D H 1 R 132 H mutation increases radiosensitivity in mild hypoxic conditions.